Penyelesaian Kasus Pelecehan Seksual Di Kepulauan Kei Maluku Tenggara (Suatu Kejian Hukum Adat) - Julia Afniasary Sulaiman; Reimon Supusepa; Steven Makaruku (Faculty of Law Universitas Pattimura, 2023)
Indonesia is based on the rule of law, but acts that violate the law often occur, one of which is sexual harassment. The phenomenon of sexual harassment often occurs in society, both physically and non-physically, in other words, there are still many who violate the rules that have been made. In the issue of sexual harassment, gender reactions are complex and involve various aspects of human life such as morals, religion, and others. The type of research used by the author in preparing this writing is normative juridical legal research (normative legal research method). The normative juridical research method is legal research of libraries or secondary lists only. This research was conducted in order to obtain materials in the form of theories, concepts, legal principles and legal regulations related to the subject matter. Research approach methods, namely the statute approach and the case approach. The results of the research concluded that laws governing women's rights to honor and dignity include prohibitions against hissing at women, pinching and defiling women. There are values ​​such as respect for the rights and dignity of women so that the slightest action that can hurt feelings or is intended to tempt women is strictly prohibited.